PREVENTION OF GRAPE CROWN GALL - N. Limanska (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2012)
Complex strategies to control crown gall are reviewed: indexing of planting material, hot water treatment, cultural practices, treatments with chemical substances and plant extracts. Special attention is paid to the biological control. The short descriptions of the most well studied antagonistic strains are listed. The main problems of grape crown gall prevention are elucidated.